Addition of Chitosan Concentration on Mechanical Properties of Yam Yam (Pachyrhizus Erosus) Starch Edible Film - Hidayah, Nurul; Dewata, Indang (Jurnal Kependudukan dan Pembangunan Lingkungan, 2022)
Edible film is a thin layer used to protect food products whose basic ingredients are environmentally friendly natural ingredients. This study aims to determine the effect of chitosan addition of chitosan on edible films made from yam starch (Pachyrhizus erosus) on the physical and mechanical properties of edible films. In this study using polyethylene glycol plasticizer and variations in the addition of chitosan concentration (0%, 0.5%, 1%, 1.5%, 2%). cm-1, C-H bonds in wave numbers 3000 – 2840 cm-1 and C-O bonds in wave numbers 1085 – 1050 cm-1. The results obtained were compared with starch and the results obtained were almost the same as starch standards. The mechanical properties of the maximum tensile strength with the addition of 1% chitosan was 7.091 Mpa, the maximum elongation with the addition of 2% chitosan was 2.3 and the maximum elasticity with the addition of 1% chitosan was 864 Mpa. The mechanical properties of the edible film obtained for tensile strength and elasticity have met the standards set by the Japanese Industrial Standard (JIS) while the elongation value has not met the standards.